Phase I trial of concurrent stereotactic body radiotherapy and nelfinavir for locally advanced borderline or unresectable pancreatic adenocarcinoma. (March 2019) - Lin, Chi; Verma, Vivek; Ly, Quan P.; Lazenby, Audrey; Sasson, Aaron; Schwarz, James K.; Meza, Jane L.; Are, Chandrakanth; Li, Sicong; Wang, Shuo; Hahn, Stephen M.; Grem, Jean L.
Highlights: No studies have assessed SBRT + NFV for borderline/unresectable pancreatic cancer. This phase I trial enrolled 46 patients, of which 39 received per-protocol therapy. 40 Gy SBRT and 1250 mg BID ×5wks NFV was the maximum tolerated dose. Six (15%) patients recurred locally, and median overall survival was 14.4 months. Attention to treatment planning may reduce the incidence of late GI bleeding. Abstract: Introduction: The HIV protease inhibitor nelfinavir (NFV) displays notable radiosensitizing effects. There have been no studies evaluating combined stereotactic body radiotherapy (SBRT) and NFV for borderline/unresectable pancreatic cancer. The primary objective of this phase I trial (NCT01068327) was to determine the maximum tolerated SBRT/NFV dose, and secondarily evaluate outcomes. Methods: Following initial imaging, pathologic confirmation, and staging laparoscopy, subjects initially received three 3-week cycles of gemcitabine/leucovorin/fluorouracil; patients without radiologic progression received 5-fraction SBRT/NFV. Dose escalation was as follows: (1) 25 Gy/625 mg BID ×3wks; (2) 25 Gy/1250 mg BID ×3wks; (3) 30 Gy/1250 mg BID ×3wks; (4) 35 Gy/1250 mg BID ×3wks; (5) 35 Gy/1250 mg BID ×5wks; and (6) 40 Gy/1250 mg BID ×5wks. Pancreaticoduodenectomy was performed thereafter if resectable; if not, gemcitabine/leucovorin/fluorouracil was administered. Results: Forty-six patients enrolled (10/2008-5/2013); 39 received protocol-directed therapy. Sixteen (41%) experienced any grade ≥2 event during and 1 month after SBRT. Four grade 3 and both grade 4 events occurred in a single patient at the initial dose level. 40 Gy/1250 mg BID ×5wks was the maximum tolerated dose. Five patients had late gastrointestinal bleeding ( n  = 2 superior mesenteric artery pseudo-aneurysm, n  = 1 disease progression, n  = 1 lower GI tract, n  = 1 unknown location). The median overall survival was 14.4 months. Six (15%) patients recurred locally; median local failure-free survival was not reached. The median distant failure-free survival was 11 months, and median all failure-free survival was 10 months. Conclusions: Concurrent SBRT (40 Gy)/NFV (1250 mg BID) for locally advanced pancreatic cancer is feasible and safe, although careful attention to treatment planning parameters is recommended to reduce the incidence of late gastrointestinal bleeding.